Comparative assessment of intraocular inflammation following standard or heavy silicone oil tamponade: a prospective study. Issue 1 (4th June 2018) - Semeraro, Francesco; Russo, Andrea; Morescalchi, Francesco; Gambicorti, Elena; Vezzoli, Sara; Parmeggiani, Francesco; Romano, Mario R.; Costagliola, Ciro
Abstract: Purpose: To evaluate the inflammation associated with the use of standard silicone oil (polydimethylsiloxane; PDMS) and heavy silicone oil (HSO) Densiron‐68™ in patients undergoing vitrectomy for retinal detachment. Materials and Methods: A prospective study was performed involving 35 patients scheduled to undergo vitrectomy for retinal detachment. Patients received PDMS or Densiron‐68™ HSO according to superior or inferior retinal localization of the tears, respectively. For assessing the inflammation, prostaglandin E2 (PGE2 ) and interleukin‐1 α (IL‐1 α ) levels were evaluated in the aqueous. Results: Thirty‐five eyes of 35 patients completed the study: 20 eyes received HSO, and 15 eyes received PDMS. The mean aqueous PGE2 level was significantly higher in HSO patients than in PDMS patients (869.16 ± 242.83 pg/ml versus 369.38 ± 209.7 pg/ml, respectively; p < 0.0001). The mean aqueous IL‐1 α level was also significantly higher in HSO patients than in PDMS patients (81.40 ± 36.9 pg/ml versus 40.8 ± 32.5 pg/ml, respectively; p = 0.002). In HSO, a moderate positive correlation between the endotamponade duration and both PGE2 ( r  = 0.44; p = 0.05) and IL‐1 α ( r  = 0.48; p = 0.033) levels was observed. In PDMS, a strong positive correlation between the endotamponade duration and both PGE2 ( r  = 0.89; p < 0.0001) and IL‐1 α ( r  = 0.68; p = 0.006) levels was observed. Conclusion: Although both HSO and PDMS yielded favourable success rates in the surgical treatment of complicated retinal detachments, HSO triggered a more severe inflammatory reaction, in a time‐dependent manner.